2012
DOI: 10.1007/s10847-012-0230-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of the inclusion compounds of thymol, carvacrol and eugenol in β-cyclodextrin by X-ray crystallography

Abstract: The crystal structures of the inclusion compounds of thymol, carvacrol and eugenol, (components of essential oils of vegetable origin) in -cyclodextrin have been determined. Thymol/-CD crystallizes in the space group P1 containing two host molecules in its asymmetric unit whereas both carvacrol/-CD and eugenol/-CD complexes crystallize in the space group C2. In all three complexes two host molecules form head-to-head dimers their guest/host stoichiometry being: 1/2 (carvacrol/-CD), 2/2 (thymol/-CD) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…Peaks corresponding to β-CD and free thymol were also detected in the spectrum. The 1:1 mole ratio observed for the thymol/β-CD in the current study is consistent with the work of Bethanis et al (2013) who determined a 1:1 mole ratio of thymol/β-CD in the solid state using x-ray crystallography. Although the qualitative analysis using ES/MS indicates that thymol was complexed with β-CD, the results do not enable the efficiency of the process to be determined and so a quantitative analysis using GC was used to assess the IE.…”
Section: Pre-optimised Complex Yield and Inclusion Efficiencysupporting
confidence: 92%
See 1 more Smart Citation
“…Peaks corresponding to β-CD and free thymol were also detected in the spectrum. The 1:1 mole ratio observed for the thymol/β-CD in the current study is consistent with the work of Bethanis et al (2013) who determined a 1:1 mole ratio of thymol/β-CD in the solid state using x-ray crystallography. Although the qualitative analysis using ES/MS indicates that thymol was complexed with β-CD, the results do not enable the efficiency of the process to be determined and so a quantitative analysis using GC was used to assess the IE.…”
Section: Pre-optimised Complex Yield and Inclusion Efficiencysupporting
confidence: 92%
“…x-ray crystallographic studies of Bethanis et al (2013) who reported a 1:1 mole ratio for thymol/β-CD and Ceborska (2016) who reported a 2:2 molar ratio for the (-)-linalool/β-CD dimer. It is interesting to note, however, that the X-ray crystallographic study by Bethanis et al (2013) suggests that a 1:2 carvacrol/β-CD ratio exists in the solid state where the complex was produced using a guest/host molar ratio of 1.5:1. Under the synthesis conditions used in the current work, if a complex was formed having a 1:2 mole ratio of guest/host then that would result in an observed IE of only 50% (w/w) so clearly a 1:2 complex was not obtained in the present study.…”
Section: Optimised Inclusion Of Thymol Carvacrol and Linaloolmentioning
confidence: 99%
“…Bethanis et al [39] and Mulinacci et al [40] demonstrated through different methods that the CARV is found fully immersed inside the hydrophobic cavity of b-CD. This complex, when prepared with the co-precipitation method in aqueous solution, gives a complex monomer of 1/1 stoichiometry, in which the isopropyl group of the CARV is located closer to the larger side of the hydrophobic cavity of b-CD.…”
Section: Discussionmentioning
confidence: 99%
“…Thyme oil, composed of thymol (44.88%) and carvacrol (4.6%), was applied to MCT-CDfabrics in defined conditions to prevent evaporation of the label components. The oil application was made with the assumption that β-CD can encapsulate carvacrol and thymol [34,[50][51][52]. In fact, the interaction of β-CD and carvacrol in aqueous solution, results in a 1:1 complex, in which the isopropyl group of the molecule is located closer to the larger side of the hydrophobic cavity of β-CD.…”
Section: Functionalization Of Cotton With Mpcm Mct-β-cd and Thyme Oilmentioning
confidence: 99%